Photophysical Properties of Pheophorbide-a Derivatives and Their Photodynamic Therapeutic Effects on a Tumor Cell Line In Vitro. (10th August 2014) - Wang, Kang-Kyun; Li, Jing; Kim, Bong-Jin; Lee, Jeong-Hyun; Shin, Hee-Won; Ko, Si-Hwan; Lee, Won-Young; Lee, Chang-Hee; Jung, Seok Hoon; Kim, Yong-Rok
Abstract : Pheophorbide-a derivatives have been reported to be potential photosensitizers for photodynamic therapy (PDT). In this study, photophysics of pheophorbide-a derivatives (PaDs) were investigated along with their photodynamic tumoricidal effect in vitro . PaDs were modified by changing the coil length and/or making the hydroxyl group (–OH) substitutions. Their photophysical properties were studied by steady-state and time-resolved spectroscopic methods. The photodynamic tumoricidal effect was evaluated in the mouse breast cancer cell line (EMT6). Lifetime and quantum yield of fluorescence and quantum yields of triplet state and singlet oxygen were studied to determine the dynamic energy flow. The coil length of the substituted alkyl group did not significantly affect the spectroscopic properties. However, the substitution with the hydroxyl group increased the quantum yields of the triplet state and the singlet oxygen due to the enhanced intersystem crossing. In order to check the application possibility as a photodynamic therapy agent, the PaDs with hydroxyl group were studied for the cellular affinity and the photodynamic tumoricidal effect of EMT6. The results showed that the cellular affinity and the photodynamic tumoricidal effect of PaDs with the hydroxyl group depended on the coil-length of the substituted alkyl group.